Nicaragua y una ventana al mundo La revista Ventana (1960-1963) - Moro, Diana (2019)
In the 1960s, in Nicaragua, the magazine Ventana directed by young university students, Sergio Ramírez and Fernando Gordillo, became a political and literary sounding board. The political debate and claim of freedom and autonomy in the context of the dictatorship came together with a broad and cosmopolitan literary commitment. A multiplicity of authors and literary texts from different languages and cultures came together.